The impacts of democratic learning environment on students’ self-enhancement: a case study in a Malaysian public university - Hamzah, Lina Mursyidah; Majid, Sheikha; Mohd Yusof, Norhayati; Hussien, Suhailah (UiTM Press, 2024)
An educational institution is one of the places where students can work on their self-enhancement. This is because an educational institution is more than just a place to gain knowledge; it is also a place to grow as an individual holistically. This study explored to what extent a democratic learning environment can impact students’ self-enhancement. For this purpose, the study adopted a qualitative study with a case study as the research design. Using semi-structured interviews, six participants who had experienced the democratic classroom approach in their courses were involved. The data from the interviews were then analysed using thematic analysis. Three major themes were drawn from the interviews of the participants. The findings of the study showed that when the students experienced a democratic classroom approach in their courses, they felt appreciated, and their sense of confidence and belonging increased. Therefore, the study suggests that educators need to know how to foster students’ self-enhancement to improve their well-being while engaging in teaching and learning activities.